Supplier integration roles in new product development: The automotive suppliers’ perspective - Kanapathy, Kanagi; Chu, K.O. (2019)
This research examined supplier integration in New Product Development (NPD) from the suppliers’ perspectives. The level of supplier involvement in NPD practices and the drivers and barriers of supplier integration in NPD were explored. In this case study based qualitative research; data were gathered from interviews conducted with ten automotive suppliers directly involved in NPD with customer firms. The suppliers to national automakers acquired higher level of integration (in terms of design responsibility, product complexity, specifications provides, influences on specifications, stage of involvement, component testing responsibility, and technological capacities) compared to the suppliers to MNC automakers. Market competition was found to be the main driver for suppliers’ involvement in NPD while limited knowledge transfer was the major barrier for suppliers’ NPD integration with customers.